Health-promoting lifestyle behaviors and their associated factors among pregnant women in Debre Markos, northwest Ethiopia: a cross-sectional study - Mihiret, Getachew Tilaye; Meselu, Belsity Temesgen; Wondmu, Kumlachew Solomon; Getaneh, Temesgen; Moges, Nurilign Abebe (Frontiers in Global Women's Health, 2025)
IntroductionPromoting healthy lifestyle behaviors during pregnancy is a crucial health promotion strategy that could reduce pregnancy-related complications that may harm women and their fetuses. However, very few studies have assessed the prevalence of health-promoting lifestyle behaviors among pregnant women in Ethiopia. This study aimed to evaluate the extent and associated factors of health-promoting lifestyle behaviors among pregnant women in public health institutions in Debre Markos, northwest Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among 275 pregnant women who were recruited using a systematic random sampling technique from 19 April to 19 May 2021. A face-to-face interview-administered questionnaire was used to collect the data. The data were analyzed using SPSS version 25. Multivariable binary logistic regression was used to identify the factors associated with the outcome variable. adjusted odds ratio (AOR), with a 95% confidence interval (CI) were used to measure the strength of the associations at a p-value <0.05.ResultsThe average mean score for health-promoting lifestyle behaviors was 2.68 (±0.38). Factors such as rural residency (AOR = 0.29; 95% CI = 0.10–0.82), family size (≥5) (AOR = 0.25; 95% CI = 0.08–0.79), being the decision-maker for economic expenses (AOR = 0.34; 95% CI = 0.14–0.84), and average monthly income (AOR = 0.15; 95% CI = 0.04–0.59) were found to be significantly associated with health-promoting lifestyle behaviors during pregnancy.ConclusionApproximately two-thirds of participants demonstrated better (healthier) health-promoting lifestyle behaviors during their pregnancy. To reduce unhealthy lifestyle-related maternal morbidity and mortality in Ethiopia, it is important to encourage health-promoting activities through health education and antenatal care follow-up with an emphasis on women who reside in rural areas, and who have a high family size, low income level, and have husbands who are the primary decision-makers for their economic expenses.